Dynamic relationships of capital flight and macroeconomic fundamentals in Malaysia - Noor Azryani Auzairy; Chan Soh Fun; Tan Li Ching; Soo Bow Li; Chua Siew Fung (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Understanding the very factors that influence massive capital outflow from an economy is vitally important as it may assist decision makers in formulating effective strategies which can not only mitigate such capital flight but also slow down the deterioration of the economy and even re-generate it. This paper analyzed the dynamic interaction between macroeconomic fundamentals and capital flight using co-integration and vector auto-regression. The macroeconomic fundamentals considered were exchange rates, consumer price index, gross domestic products and interest rates. The results show that macroeconomic fundamentals and capital flight are associated in the long run. In terms of short-run dynamics and interactions between capital flight and macroeconomic fundamentals, variations in capital flight are predominantly attributed to its own variations and exchange rate variations. Innovations in capital flight explain substantial fractions of the GDP, exchange rate, interest rate and CPI variations.